A Practical Guide for Using Generative AI in Academic Research. - Clark, Kevin R. (Radiologic Technology)
The article focuses on the integration of generative artificial intelligence (AI) in academic research, highlighting its applications in idea generation, literature review, data analysis, manuscript writing, source citation, and grant writing. While these AI tools can enhance efficiency and accessibility, the article emphasizes the necessity of critical oversight to ensure academic integrity, as researchers remain responsible for validating the accuracy and originality of AI-generated content. It also discusses the ethical considerations and publisher guidelines that researchers must follow when utilizing AI technologies, underscoring the importance of transparency in disclosing AI usage in scholarly work. Additionally, the article addresses the environmental implications of AI and the ongoing efforts to establish sustainable practices in its application.